Business Identity Branding Strategy to Enhance The Competitiveness And Sales Performance of The Kodam Coffee MSMEs (Bangun Jaya, Tambusai Utara, Rokan Hulu, Riau) - Yogi Mayhenra; Doni Nazahendra; Ikmal (International Journal of Economic and Tourism Research, 2025)
In the face of increasingly fierce competition, the development of micro, small and medium enterprises (MSMEs) in Indonesia requires the implementation of an effective branding strategy to strengthen business identity. This research was conducted with the aim of analyzing the effect of business identity branding strategies on increasing competitiveness and sales volume at Kodam Coffee MSMEs. A qualitative approach has been applied in this study, with data collection techniques including in-depth interviews, participatory observation, and analysis of related documents. The results showed that the branding strategy which includes the establishment of a logo, packaging design, brand narrative, as well as the utilization of digital marketing has successfully differentiated Kodam Coffee from its competitors. The resulting positive impacts include increased brand awareness, the formation of customer loyalty, and significant sales growth. Based on these findings, it can be concluded that the consistent and planned implementation of branding strategies plays an important role in improving the competitiveness and sales performance of MSMEs, particularly in the coffee industry sector.